Allelic variation for GS and GOGAT genes in a tetraploid wheat collection - Nigro D.; Giancaspro A.; Giove S.L.; Piarulli L.; Marcotuli I.; Mangini G.; Blanco A. (Proceedings of the International Symposium on Genetics and breeding of durum wheat, 2014)
Nitrogen is one of the major limiting nutrients in most plant species and is mostly assimilated as reduced form of ammonium. Ammonium is assimilated into amino acids through the synergic activity of two enzymes: glutamine synthetase (GS) and glutamate synthase (GOGAT). While Glutamine synthetase genes are a gene family whose enzymes are located in both cytoplasm (GS1, GSe and GSr) and plastids (GS2), glutamate synthase exists in two different isoform depending on the electron donor used as cofactor: NADH- dependent and Fd- dependent GOGAT, both active in plastids. GS catalyses the incorporation of ammonium into glutamate, producing glutamine. GOGAT catalyses the transfer of the amide group of glutamine to 2-oxoglutarate, resulting in the formation of two molecules of glutamate. This assimilation requires cofactors, reducing equivalents and other compounds generated during photosynthesis. Glutamine and glutamate serve as nitrogen donors for the biosynthesis of many other molecules, mainly for amino acid, directly involved in protein biosynthesis and ultimately in grain protein content. The aim of the present work was to assess the correlation between grain protein content and GS genes through identification of new allelic variations in a collection of durum wheat genotypes. For this purpose a collection of 240 tetraploid wheat genotypes (Triticum turgidum L.), was analyzed allowing the identification of 5 different haplotypes for the genes GS2-A2 and GS2-B2 of which the “a” allele of GS2-A2 was found significantly correlated with grain protein content.
International Symposium : Genetics and Breeding of Durum Wheat, 2013/05/27-30, Rome (Italy)